Internet Of Things (IoT)-Based Smart Garden And Automatic Irrigation System - Mohamad Harith Aizat, Suhaili (2023)
Carbon dioxide, water, and sunlight are three essential elements for plants. Water is crucial for nutrient transport and the process of photosynthesis. Insufficient water can result in plant death, while excessive water can lead to root suffocation and decay. The existing system lacks an alert system to notify users, and it also doesn't provide accurate, real-time data on gardens. Thus, due to the weakness of the existing system, the thesis proposes Internet of Things (IoT) – Based Smart Garden & Automatic Irrigation System. In the proposed system, ESP32 is the main board along with three sensors which are soil moisture sensor, temperature & humidity sensor, and PIR motion sensor. The objective of this proposed system is to use internet-connected devices to monitor and control various aspects of a garden, including soil moisture, temperature & humidity, and motion. The goal is to automate and optimize the gardening process, resulting in healthier plants and more efficient resource utilization. Additionally, it provides remote monitoring and control capabilities for the user. Rapid Application Development is used as a guiding principle to complete the proposed system, enabling quick and efficient development with the ability to make changes and adjustments based on user feedback. Data is collected and can be accessed via a Blynk application, and if the soil moisture falls below a certain level, the water pump will activate automatically. The system also monitors humidity and temperature levels and turns on the fan to cool down as needed. Also, the system will detect motion and will warn the user about the intruder. Based on the Internet of Things (IoT), the system utilizes the ESP32 and Blynk application for data exchange and communication with a smartphone application. Conclusion, the proposed system aims to meet its objectives and significantly improve the gardening experience by making it more efficient, convenient, and data driven.